LOCAL HYPERTHERMIA IN COMBINED MODALITY TREATMENT OF LARYNGEAL AND LARYNGOPHARYNGEAL CANCER - Е. L. Choynzonov (Sibirskij Onkologičeskij Žurnal, 2016)
Preliminary treatment outcomes for 35 patients with stage T1–3N0–2M0 laryngeal and laryngopharyngeal cancer have been presented. Out of 35 patients, there were 30 with laryngeal cancer and 5 with laryngopharyngeal cancer. Combined modality treatment including preoperative radiation therapy was administered to 16 patients and radical radiotherapy (without surgery) was given to 19 patients. Radiotherapy response was assessed in patients treated with total doses of 40 Gy and 60 Gy. Local hyperthermia resulted no in expressed general and local reactions. Patients with laryngeal and laryngopharyngeal cancer and tumor regression of less than 50 % or stable disease underwent surgery. Histological examination revealed complete response in all cases. Patients with laryngeal and laryngopharyngeal cancer and tumor regression of more than 50 % received radical radiation therapy in combination with local hyperthermia. The analysis of treatment outcomes indicates that local hyperthermia allows the rate of complete response to be increased.